Sistem Informasi Presensi Pegawai pada Sprint Digital Printing Berbasis Web Menggunakan Metode Agile - Wijaya, Tan Steven; Abdillah, M. Zakki (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
In the era of digitalization, the presence of an efficient information system is very important to support company operations. The web-based employee attendance information system at Sprint Digital Printing is designed to make it easier to record and monitor employee attendance in real-time. The development of this system uses the Agile method, which allows flexibility and responsiveness to changing needs during the development process. The Agile method was chosen because of its iterative characteristics, so that any changes or adjustments can be accommodated immediately without disrupting the entire project. This attendance information system was developed using the PHP and MySQL programming languages for database management, with the Codeigniter framework. This system provides features such as attendance recording, performance reports, and automatic notifications, all of which can be accessed via the web platform. By implementing this system, operational efficiency increases, reduces manual errors in recording attendance, and makes it easier for management to evaluate employee performance. The results of this development show that a web-based attendance information system can increase productivity and accuracy of attendance data at Sprint Digital Printing.